What learning environments help improve decision-making? - O`Connor, D.; Larkin, P.; Williams, A. M. (Physical Education and Sport Pedagogy, 2018)
Background: Decision-making is a key component of performance in sport. However, there has been minimal investigation of how coaches may adapt practice sessions to specifically develop decision-making.